2020
DOI: 10.1186/s12875-020-01308-5
|View full text |Cite
|
Sign up to set email alerts
|

Are general practitioners referring patients with low back pain for CTs appropriately according to the guidelines: a retrospective review of 3609 medical records in Newfoundland using routinely collected data

Abstract: Background CT Imaging is often requested for patients with low back pain (LBP) by their general practitioners. It is currently unknown what reasons are common for these referrals and if CT images are ordered according to guidelines in one province in Canada, which has high rates of CT imaging. The objective of this study is to categorise lumbar spine CT referrals into serious spinal pathology, radicular syndrome, and non-specific LBP and evaluate the appropriateness of CT imaging referrals from general practit… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
8
0

Year Published

2022
2022
2023
2023

Publication Types

Select...
7
1

Relationship

1
7

Authors

Journals

citations
Cited by 13 publications
(8 citation statements)
references
References 21 publications
0
8
0
Order By: Relevance
“…An evidence synthesis of studies published between 1995 and 2012 found for the treatment of acute/subacute LBP DCs had the highest percentage of concordance with CPGs (70.2%) followed by PTs (63.1%) and medical physicians (47.1%) [17]. Individual studies typically focused on a single type of health care provider (HCP) like; primary care physicians [18,19], chiropractors (DCs) [20], physical therapists (PTs) [21][22][23], or surgeons [24]). Real-world guideline concordance could not be assessed in cross-sectional surveys that used clinical vignettes [20][21][22][23].…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…An evidence synthesis of studies published between 1995 and 2012 found for the treatment of acute/subacute LBP DCs had the highest percentage of concordance with CPGs (70.2%) followed by PTs (63.1%) and medical physicians (47.1%) [17]. Individual studies typically focused on a single type of health care provider (HCP) like; primary care physicians [18,19], chiropractors (DCs) [20], physical therapists (PTs) [21][22][23], or surgeons [24]). Real-world guideline concordance could not be assessed in cross-sectional surveys that used clinical vignettes [20][21][22][23].…”
Section: Introductionmentioning
confidence: 99%
“…Real-world guideline concordance could not be assessed in cross-sectional surveys that used clinical vignettes [20][21][22][23]. Retrospective cohort studies focused on specific services e.g., imaging utilization [18,19] or multiple service outcomes but were not subdivided by initial HCP type [24].…”
Section: Introductionmentioning
confidence: 99%
“…To comprehensively define the cohort and their past medical histories would require interrogation of additional data sources; however, previous attempts at such an investigational approach have revealed vital data remains missing. 26 The size of the cohort selected for this preliminary study resulted in small subgroup sizes (post-hoc analysis suggests that increasing the sample size to 228 patients per subgroup would enable detection of statistically significant differences); however, the pilot study has revealed some useful data and trends in radiological investigations and practice in primary care. One unexpected finding was that 28 patients had undergone interventional spinal therapeutic procedures using image guidance.…”
Section: Patient Subgroup 1 Patient Subgroup 2 Patient Subgroupmentioning
confidence: 97%
“…In the province of NL, medical practitioners (e.g., general practitioners) and chiropractors are able to order x-rays and regularly manage patients with LBP [ 20 ]. Based on a medical record review from GPs in NL, only 6.5% of referrals for lumbar spine CT imaging were considered appropriate (i.e., concordant with guideline or best practice recommendations) [ 21 ]. Among chiropractors in NL, a survey on their knowledge of and adherence to radiographic guidelines found that about half of respondents were unaware of or did not know current guideline recommendations for LBP radiography, and one quarter of respondents indicated they did not use guidelines to inform their clinical decisions [ 22 ].…”
Section: Introductionmentioning
confidence: 99%